Description of a new infaunal shrimp species (Decapoda: Alpheidae: Salmoneus) from the Atlantic coast of Florida - Anker, Arthur; Scioli, Justin A. (Zootaxa, 2025)
A new alpheid shrimp, Salmoneus manningi sp. nov., is described based on material collected in the Indian River Lagoon on the Atlantic coast of Florida, USA. In addition, one of the two paratypes of S. cavicolus Felder & Manning, 1986 is assigned to the new species. All specimens of S. manningi sp. nov. were extracted from burrows using a suction pump, sometimes together with the burrowing mantis shrimp, Lysiosquilla scabricauda (Lamarck, 1818), suggesting a possible symbiosis between these two crustaceans. Although S. manningi sp. nov. is morphologically similar to S. cavicolus, the two species do not appear to be closely related. In addition, S. cavicolus is reported from several new localities in the Indian River Lagoon and its previously unknown burrowing host is shown to be Alpheus floridanus Kingsley, 1878.